Drug-induced hypersensitivity syndrome with high procalcitonin levels due to piperacillin/tazobactam and meropenem: A case report - Song, Gao; Cheng, Meng-Qun; Li, Rong; Zhang, Cai-Qiong; Sun, Ping (Frontiers in Medicine, 2022)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare and life-threatening adverse drug reaction. It is characterized by a long latency period with rash, hematological abnormalities, and visceral damage. Clinical manifestations of DRESS vary. Thus, accurate clinical diagnosis and identification are essential to ensure timely treatment commencement for improving prognosis and speeding up recovery. We report the case of a 66-year-old male patient with drug reaction induced by a beta-lactam antibiotic, piperacillin/tazobactam (Pip/Taz). This resulted in the manifestation of both eosinophilic and systemic symptoms. Ten days after Pip/Taz treatment commencement, the patient developed hyperthermia and elevated serum procalcitonin (PCT), leading to a misdiagnosis of an exacerbated infection. Meropenem treatment was then started. However, after 72 hours, the patient developed generalized rash, eosinophilia, hematological abnormalities, and visceral damage. Moreover, PCT levels were significantly elevated. All these symptoms were associated with DRESS. The sensitizing drug was discontinued, and glucocorticoids were administered, resulting in gradual subsiding of symptoms and decreases in serum PCT levels. Clinicians should be aware that elevated PCT serum levels may be a diagnostic biomarker for DRESS, which requires specific treatment. Furthermore, studies are warranted to further evaluate and elucidate the role of PCT in response to DRESS.